Consumer Demand Behavior for Refilled Gallon Water in Urban MSMEs: Empirical Evidence from Sonaf Maneka Depot in Kupang City (Jurnal Ekonomi Pembangunan Widya Mandira, 2026)
Refillable gallon water has become a preferred choice for many urban households because it is more easily accessible and relatively more affordable than branded bottled drinking water. However, demand for this product is not always stable. This condition is evident at the Sonaf Maneka Depot in Kupang City, which has active customers and documented monthly sales data for 2024, yet shows significant fluctuations in sales despite drinking water being a basic necessity. This study aims to explain the factors that shape consumer demand by positioning price, household income, number of family members, product quality, and service as explanatory constructs. The research employs a descriptive quantitative approach. The study population consists of 350 active customers, while 78 respondents were determined using the Slovin formula. Data were collected through questionnaires, observation, and documentation, and then analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS. The results of the structural model evaluation indicate that consumer demand is primarily shaped by perceptions of reasonable pricing and convenient service. Service is the strongest factor in explaining demand, followed by price. Household income, number of family members, and product quality have not yet become direct determinants in the research model. These findings emphasize that for refillable drinking water SMEs, strategies to maintain demand should not rely solely on maintaining product quality, but must also focus on pricing that aligns with purchasing power and on service that is fast, responsive, and consistent.
Keywords: Consumer Demand; Price; Service; Refill Gallon Water; MSMEs